2022
DOI: 10.3390/cells11172713
|View full text |Cite
|
Sign up to set email alerts
|

An Epitope-Specific LGI1-Autoantibody Enhances Neuronal Excitability by Modulating Kv1.1 Channel

Abstract: Leucine-rich Glioma-Inactivated protein 1 (LGI1) is expressed in the central nervous system and its genetic loss of function is associated with epileptic disorders. Additionally, patients with LGI1-directed autoantibodies have frequent focal seizures as a key feature of their disease. LGI1 is composed of a Leucine-Rich Repeat (LRR) and an Epitempin (EPTP) domain. These domains are reported to interact with different members of the transsynaptic complex formed by LGI1 at excitatory synapses, including presynapt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 21 publications
(38 reference statements)
3
9
0
Order By: Relevance
“…Previous studies showed simultaneous occurrence of both epitope-specific LGI1 antibodies in patients with LGI1 encephalitis with an increased ratio of LRR-specific IgG. 20 From our data and other reports investigating epitope-specific effects of LGI1 mAbs, 15 , 21 , 42 LRR-specific IgG might be more effective in inducing hyperexcitability and possibly leading to seizure initiation. However, larger patient cohorts need to be investigated to evaluate the relative contribution of epitope-specific IgG antibodies for disease symptom development.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…Previous studies showed simultaneous occurrence of both epitope-specific LGI1 antibodies in patients with LGI1 encephalitis with an increased ratio of LRR-specific IgG. 20 From our data and other reports investigating epitope-specific effects of LGI1 mAbs, 15 , 21 , 42 LRR-specific IgG might be more effective in inducing hyperexcitability and possibly leading to seizure initiation. However, larger patient cohorts need to be investigated to evaluate the relative contribution of epitope-specific IgG antibodies for disease symptom development.…”
Section: Discussionsupporting
confidence: 66%
“…These results obtained in primary neurons corroborate observations obtained in rat hippocampal slice cultures using similar patient-derived mAbs against LRR and EPTP, which have been attributed to reduced K v 1 channel–mediated I D current. 42 This has been substantiated here and in slice cultures 20 by reduced slope of ramp-like depolarization of subthreshold response at prerheobase current step injection (see also Refs. 20 , 29 , 30 for using this measure) and in recent studies by diminished effects of the K v 1.1-specific channel blocker dendrotoxin K. 20 , 42 This view is also supported by LRR-specific antibodies that may prevent the interaction of LGI1 to the K v β subunits, resulting in the transformation of slowly inactivating D-type currents into rapidly inactivating A-type currents, as shown in an in vitro model.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Slices cultures were prepared as described previously (Debanne et al, 2008; Extrémet et al, 2022). Young Lgi1 KO mice (P7–P10) were killed by decapitation, the brain was removed, and each hippocampus dissected.…”
Section: Methodsmentioning
confidence: 99%